UPACARA DAN MAKNA MINUM TEH BAGI MASYARAKAT TIONGHOA - Asty Perbina Ginting (Jurnal Pustaka Nusantara dan Budaya, 2013)
The  title of this research is “ Upacara dan Makna Minum Teh bagi Masyarakat Tionghoa”. In this research, the writer describes the tradition and meaning of Tea Ceremony in ethnic Tionghoa. Due to title, there are some concepts written in chapter two, they are ceremony, kind of tea and ethnic Tionghoa. The theory used in this paper are functionalism and ceremony is whichare applied for the analysis of function and meaning of tea ceremony in Chinese tradition. The methodology used in this research is descriptive. The result of the analysis shows that the tea ceremony, usually celebration in Chinese tradition, such as wedding ceremony, gong fu cha ceremony, dao cha ceremony, wu wo ceremony and ancestor veneration ceremony. The it concludes that tea ceremony shows that tea ceremony is very important in chinese tradition and give some meaning. Key Word: tea ceremony; Chinese tradition; tea ceremony influence